Obesity Reduces Cognitive and Motor Functions across the Lifespan - Chuanming Wang; John S. Y. Chan; Lijie Ren; Jin H. Yan (Neural Plasticity)
Due to a sedentary lifestyle, more and more people are becoming obese nowadays. In addition to health-related problems, obesity can also impair cognition and motor performance. Previous results have shown that obesity mainly affects cognition and motor behaviors through altering brain functions and musculoskeletal system, respectively. Many factors, such as insulin/leptin dysregulation and inflammation, mediate the effect of obesity and cognition and motor behaviors. Substantial evidence has suggested exercise to be an effective way to improve obesity and related cognitive and motor dysfunctions. This paper aims to discuss the association of obesity with cognition and motor behaviors and its underlying mechanisms. Following this, mechanisms of exercise to improve obesity-related dysfunctions are described. Finally, implications and future research direction are raised.